2015
DOI: 10.2147/ijwh.s90772
|View full text |Cite
|
Sign up to set email alerts
|

To what extent will women accept HPV self-sampling for cervical cancer screening? A qualitative study conducted in Switzerland

Abstract: ObjectivesHuman papillomavirus self-sampling (self-HPV) is regarded as an alternative to Pap smear testing for women who do not participate in cervical cancer screening. This qualitative study aimed to determine women’s views on cervical cancer screening and the various obstacles to participation in screening, and to evaluate the perceived benefits and disadvantages of self-HPV.MethodTwenty-four focus groups were conducted in 2012, with a total of 125 participants aged between 24 and 67 years. They were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 18 publications
2
52
0
Order By: Relevance
“…Only two studies (10.5%) demonstrated that the self-collection method exhibited low acceptability among women 9,23. The acceptability of the self-collection method among women was determined subjectively (without standardized questionnaires) in ten studies (52.6%) 10,13-16,18,20-21,23,26 and via structured and valid questionnaires in the remaining studies. Only five studies were randomized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies (10.5%) demonstrated that the self-collection method exhibited low acceptability among women 9,23. The acceptability of the self-collection method among women was determined subjectively (without standardized questionnaires) in ten studies (52.6%) 10,13-16,18,20-21,23,26 and via structured and valid questionnaires in the remaining studies. Only five studies were randomized.…”
Section: Resultsmentioning
confidence: 99%
“…The review also noted that the guidelines and explanations pertaining to the performance of the procedure played an important role in increasing patient confidence in and acceptance of the method 9,23. Therefore, the introduction of self-collection should be preceded by community education regarding both the method and the female genitourinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, many countries report suboptimal participation in screening programs [210,211,229,232,315]. In an effort to increase coverage, in addition to educational campaigns and invitation reminders, many countries are also exploring or implementing self-sampling for nonparticipants [183,204,293,307,309,323,324]. This testing strategy is also mentioned in the European Guidelines; however, they recommend that successful self-sampling pilot projects precede implementation.…”
Section: The Current Landscape Of Cervical Cancer Screening In Thementioning
confidence: 99%
“…This fact may be used to encourage women to participate in screening programs for cervical cancer [16, 17]. Nonetheless, some studies have shown that only a few women are concerned about their ability to perform self-collection correctly or they are afraid of experiencing some discomfort during the procedure [16, 18].…”
Section: Introductionmentioning
confidence: 99%